PENGARUH PERPUTARAN MODAL KERJA, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN FMCG YANG TERDAFTAR DI BEI PERIODE 2022–2025 - Annisa Wardani; Krisnawuri Handayani (Bajang Institute, 2026)
The fast-moving consumer goods (FMCG) industry is a strategic sector of the Indonesian economy, contributing significantly to domestic consumption, economic growth, and employment. Despite relatively stable demand, the industry faces increasing competition, rising production costs, and changing consumer preferences, making financial management essential for sustaining profitability. This study examines the effects of working capital turnover, capital structure, and firm size on the profitability of FMCG companies listed on the Indonesia Stock Exchange (IDX) during 2022–2025. A quantitative approach was employed using secondary data from annual financial statements. Purposive sampling produced a sample of 25 companies with 100 firm-year observations. Profitability was measured by Return on Assets (ROA), while working capital turnover, Debt-to-Equity Ratio (DER), and firm size were used as independent variables. Data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression with SPSS version 24. The results indicate that the independent variables jointly have a significant effect on profitability. Partially, working capital turnover and firm size do not significantly influence ROA, whereas capital structure has a significant negative effect. The findings suggest that excessive leverage reduces profitability, making capital structure the most influential financial determinant of performance in the FMCG sector. Therefore, companies should optimize their financing policies while maintaining effective working capital management to enhance long-term profitability